THE SURGICAL TREATMENT OF DIABETIC MACULOTHE SURGICAL TREATMENT OF DIABETIC MACULOPATHY IN PATIENTS WITH DIABETES MELLITUS TYPE 2: EFFECTIVENESS, COMPLICATIONS, RELAPSEPATHY IN PATIENTS WITH DIABETES MELLITUS TYPE 2: EFFECTIVENESS, COMPLICATIONS, RELAPSES - Yu.O. Panchenko (Медична наука України, 2019)
Relevance. It’s known a number of surgical treatment methods of diabetic maculopathy (DMP) in diabetes mellitus (DM) type 2: closed subtotal vitrectomy (CSV), which according to the testimony combined with peeling of the inner limiting membrane of the retina (ILM), panretinal laser coagulation of the retina (PRLC) and phacoemulsification of cataract (PEC).